THE INFLUENCE OF FINANCIAL LITERACY AND LIFESTYLE ON DEBT MANAGEMENT BEHAVIOR IN YOUNG MARRIED FAMILIES - Yulianah; Istiqlaliyah Muflikhati (Journal of Child, Family, and Consumer Studies, 2023)
Debt behavior often occurs when someone is in an urgent situation to meet their needs. This study aims to analyze the influence of family characteristics, financial literacy, and hedonic lifestyle on debt management behavior in young married families. The sample in this study are middle-aged women who married at the age of 19 and under and live in Jabodetabek. The sampling technique used purposive sampling method as many as 52 people who had or currently had debt. Data were processed using descriptive statistical tests and multiple linear regression tests. The level of financial literacy (knowledge, attitude, and behavior dimensions) of respondents is categorized as medium. Respondents in this study did not have a tendency to live a hedonic lifestyle. Likewise, debt management behavior is in the low category. There is a negative relationship between respondents' age and debt management behavior. The results of multiple linear regression analysis show that financial literacy (attitude dimension) has a significant effect on debt management behavior. This means that the better the respondent's attitude towards finance, the better the behavior in managing debt. Meanwhile, there is no significant influence between hedonic lifestyle and debt management behavior. Financial literacy needs to be well owned in order to create good debt management behavior.